Enactive framework for psychiatric disorders (Engrami, 2022)
The paper shows how enactivism can be used as a theoretical framework in psychiatry. An enactive approach can help solve the problem of integration in psychiatry and how to meaningfully connect the different perspectives with which we explain the causes and nature of psychiatric disorders. Enactivism allows us to comprehensively connect the phenomenological, neurophysiological, sociocultural, and existential aspects of psychiatric disorders and holistically approach their understanding and treatment. I will explain what the tenets of enactivism are, what the problem of integration in psychiatry is, and how, according to Saneke de Haan, we can provide a solution to this problem through the enactivist approach. Finally, I will suggest how enactivism can be enriched by adding an ecological perspective.
Keywords: enactivism; phenomenology; psychiatry; integration; affordance